Decoding Marxist Themes in A Bug's Life: A Study of Power, Exploitation, and Class Struggle - Johanes, Cayla Abielle; Miarso, Jessie Queen; Martin, Violet Ayuwandira Larasati (Jurnal Pendidikan Makarios, 2026)
This research aims to deep dive into the issues of class struggle, exploitation, and power, shown in the 1998 Pixar movie, “A Bug’s Life”, through the lens of Marxism theory. This analysis was conducted using the Marxist perspective from the book Das Capital, Volume I (1990) by Karl Marx. By using a qualitative close reading method, the data were collected through the deep observation of the cinematography and themes present, repeated viewing of scenes and narratives, plot and storyline reading based on the Marxism concepts to strengthen the arguments. Hence the findings show: 1) Symbolic Representation of Classes: The grasshoppers symbolize the bourgeoisie, or ruling class, which exploits the ants, representing the proletariat or working class, by taking their production without contributing to it, mirroring Marx's concept of workers being bound by "invisible threads" and working out of necessity for survival This exploitation is maintained through psychological control and fear, rather than overt physical force 2) Initial Acceptance of Oppression: The ants initially accept and believe that their oppression is the "natural order" of things before their class consciousness emerges, leading them to unite. This reflects the Marxist idea that those in power make workers believe the exploitative system is normal and necessary. The ants' fear and perceived powerlessness keep them obedient, despite their numerical superiority. 3) Empowerment through Collective Action: Once united and realizing they have nothing to lose, their group solidarity empowers them to overthrow the unnatural and exploitative system, aligning with Marx's view that the proletariat gains power through collective strength. The film highlights how fear sustains power and a rigid social hierarchy. However, achieving class consciousness enables collective action to dismantle this oppression. The main objective of this research is to uncover the themes in the story whilst making them understandable, and for readers to comprehend and to be aware of the importance of knowing social issues in movies.